Academic writing details in critical perspective - Olga A. Suleimanova; Tatiana A. Lykova (Peoples' Friendship University of Russia (RUDN University), 2023)
The article focuses on the academic writing practices in the critical perspective and is based on the error analysis of academic discourse texts represented in bachelors' and masters' qualification papers and post graduate theses. Academic writing competence is growing into an ever more deciding factor for evaluating students' performance which in the long run affects their academic prospects as well as professional career. The authors apply error analysis to detect the potential elements which may spoil the impression from the research paper, and offer some guidelines for the researchers, especially the beginners, on how to be more convincing in presenting the research results. The authors distinguish two basic types of errors, one related to stylistically relevant mistakes and the other referring to academic ethics. The former covers unnecessary negations, evaluation markers, some awkward syntactic constructions, principles of referring to scientists' names, etc. These elements are not language-dependent and are practically universal, as they can be found in any language. The authors treat the latter group as ethically-related, covering the issues of quoting format and authorial 'we'. Distinguishing metonymical malfunction is suggested when the elements of different cognitive levels are misrelated and co-located.